DEVELOPING INTERCULTURAL COMMUNICATION AND INTERCULTURAL AWARENESS IN THE EFL CLASSROOM - Cavalheiro, Lili (Estudos Linguísticos e Literários, 2020)
Throughout multiples regions around the world, waves of migrants and refugees search for better and safer living conditions. As a result, classrooms are becoming increasingly multicultural and multilingual, with many teachers feeling challenged when faced with this ‘new’ reality. Being English the most commonly shared language around the world, the English as a Foreign Language (EFL) classroom can be a ‘safe’ place where dialogue and intercultural communication are fomented. Not only can it facilitate the integration of migrant/refugee students, but it can also contribute to expanding learners’ (inter)cultural awareness and knowledge of how English may be used by multiple speakers (native and non-native) in diverse settings. In light of this, it is imperative that educators develop more inclusive English-language lessons that help break down barriers and taboos, in terms of language and culture. In order to achieve this, however, it is vital that these issues be developed at the beginning of any teacher training. Bearing this in mind, this paper begins by presenting the concept of English as a Lingua Franca and intercultural communication and follows up by reflecting upon how the traditional EFL classroom should to be reconsidered in light of today’s international role of English. Taking into account the specific growing multicultural/multilingual Portuguese context, the last section of this paper presents how these issues are developed in two pre-service MA programs in English Language Teaching at the University of Lisbon, and also how student teachers have integrated ELF-related activities/resources in their practicum, along with a commentary on their learners’ reactions.